2012
DOI: 10.1111/j.1469-0691.2012.03793.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis E virus infection in rural and urban populations, Tunisia

Abstract: Hepatitis E virus (HEV) is one of the leading agents of acute hepatitis. This study investigated the prevalence and risk factors of HEV infection in the Tunisian adult general population, either in blood donors (n=687) or in patients hospitalized for acute hepatitis (n=202). The mode of transmission differed between these two populations: contact with animals and living in a rural habitat were the main risk factors for being in contact with HEV in asymptomatic blood donors, while HEV was contracted through con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
2
8
2
Order By: Relevance
“…The present study found the anti-HEV IgG seroprevalence to be higher in male than female donors in agreement with previous studies (38)(39)(40)(41). The rate also increased with age in agreement with previous findings (37,(41)(42)(43). In this way, HEV screening in blood transfusions also should be considerate for male and over 40 years old blood donors, as they appears as a risk group.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found the anti-HEV IgG seroprevalence to be higher in male than female donors in agreement with previous studies (38)(39)(40)(41). The rate also increased with age in agreement with previous findings (37,(41)(42)(43). In this way, HEV screening in blood transfusions also should be considerate for male and over 40 years old blood donors, as they appears as a risk group.…”
Section: Discussionsupporting
confidence: 93%
“…In Northern Tunisian regions, by using the Globe Diagnostics assay, reported seroprevalences were 12;1% among pregnant women [7], 28.9% among polytransfused patients [7], 10.2% among hemodialysis patients [6] and 4,5% among blood donors [6]. A similar low prevalence of 5.4% was reported among blood donors by using the Genelabs Diagnostics assay [8]. By using a more sensitive assay, our study thus suggests that Southern Tunisia is indeed a low endemicity region for HEV.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, previous studies revealed higher rates of HEV infection in individuals with a low education level (Bortoliero et al 2006, Martins et al 2014). Additionally, other studies have reported that low educational level was statistically associated with HEV seropositivity (Junaid et al 2014, Yoon et al 2014) as well as living in rural area (Mansuy et al 2011, Houcine et al 2012). Most people who live in rural areas are farmers, suggesting potential exposure to HEV, either by contact with animals or by poor sanitary conditions (Labrique et al 2009, Goumba et al 2011, da Silva et al 2012, Junaid et al 2014).…”
Section: Discussionmentioning
confidence: 94%